RISK OF THE TRANSPORT OF DANGEROUS GOODS BY ROAD TRANSPORT IN THE CZECH REPUBLIC (Perner's Contacts, 2012)
This article is focused on the calculation of risk of traffic accidents in the transport of dangerous goods by road. There are described available statistical data on this transportation and subsequently a method for calculating the risk an ADR accident based on data obtained during a national traffic census.
Keywords: dangerous goods, accident, risk